2020
DOI: 10.2147/rmhp.s246452
|View full text |Cite
|
Sign up to set email alerts
|

<p>Relating Medical Errors to Medical Specialties: A Mixed Analysis Based on Litigation Documents and Qualitative Data</p>

Abstract: Background: We know a great deal about types, causes, and prevention of medical errors, as well as the risks of each medical specialties. Although we know something about medical errors, much remains to be done in this area particularly around effective prevention. However, little is known about whether medical errors are related to medical specialties. Our objective was to categorize and map the distribution of medical errors and analyze their relationships with medical specialties. Methods: First, public cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
(47 reference statements)
1
7
0
Order By: Relevance
“…The results reflect the content of the risk classification department of general physician medical liability insurance, which states that these specialties are characterised by high liability and high risk [ 30 , 31 ]. In particular, emergency medicine, which provides care for a wide range of undifferentiated patients, is likely to experience a high prevalence of dispute cases [ 32 ]. Therefore, specialties with a high incidence of medical errors are also vulnerable to the likelihood of errors in the clinical reasoning process [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results reflect the content of the risk classification department of general physician medical liability insurance, which states that these specialties are characterised by high liability and high risk [ 30 , 31 ]. In particular, emergency medicine, which provides care for a wide range of undifferentiated patients, is likely to experience a high prevalence of dispute cases [ 32 ]. Therefore, specialties with a high incidence of medical errors are also vulnerable to the likelihood of errors in the clinical reasoning process [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Half of these adverse events were preventable [8]. Recent data from Liu et al showed that the highest numbers of adverse events are seen in the medical specialties: general surgery, orthopaedics, and obstetrics/gynaecology [9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, if the LLIED was intramurally placed, this information is likely gleaned by EMR review. Regardless, both forms of data extraction and documentation have known deficiencies for safety screening, 15 thereby enabling an LLIED to remain inadequately recognized up to the time of (and possibly during) MRI scanning, especially in stressful emergency or trauma situations 16 , 17 . Compounding LLIED-specific potential risks from MRI exposures are unpredictable causative factors related to patient or scanning differences 4 , 6 , 9 , 12 .…”
Section: Introductionmentioning
confidence: 99%